Educational- Learning program according to some active learning strategies and its effect on the achievement of first-class students in mathematics - Hassan, Bashar Salah; Resan, Hassan Kamil (Al-Adab Journal, 2022)
The aim of the current research is to know the impact of an educational - learning program according to some active learning strategies in the achievement of students of the first intermediate grade in mathematics. To achieve this goal, the researcher chose a sample of (49) students, the experimental group (24) students and the control group (25) students from Students of the first intermediate grade in the intermediate school (Andalus for Boys) for the academic year 2020-2021 AD, and an achievement test consisting of (38) items was constructed, and the psychometric properties of the test were verified, and after processing the data statistically by using the T-test for two independent samples, the research reached:- The students of the experimental group who were taught according to the educational-learning program outperformed the students of the control group who were taught according to the usual method of achievement test.After interpreting the results, the researcher reached conclusions, made several recommendations, and proposed valid proposals for research and experimentation.